Ochrona gleb w świetle prawa krajowego i europejskiego = Protection of the soil in the light of national and european law - Kostecki, Jakub; Fruzińska, Róża (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Environmental condition of the soil is extremely important from the point of view of the living world - it?s a guarantee of environment of living and producing food. Every human activity inevitably leads to environmental degradation, including soil pollution. The degree of soil degradation and the order of its protection is a direct result of legal provisions, which is present both in the national legislation and the acts adopted at EU level. This paper presents the problem of soil protection in the files of Polish and European legislation.
Keywords: ochrona gleby; zanieczyszczenia; Polska - prawo; Europa - prawo; soil protection; soil pollution; Polish law; European law